PENGARUH AUDIT TENURE, FEE AUDIT, AUDIT DELAY, AUDIT CAPACITY STRESS TERHADAP KUALITAS AUDIT PADA KAP WILAYAH KOTA MEDAN - Zain, Jenny; Sari, Dewi Permata; Vimalananda, Yuga; Simorangkir, Enda Noviyanti; Syahputra, Oky (JURNAL LENTERA BISNIS, 2026)
Audit quality is a key element in the preparation of financial statements, as reliable financial reports serve as a foundation for decision-making. This study aims to examine the influence of Audit Tenure, Audit Fee, Audit Delay, and Audit Capacity Stress on Audit Quality. This quantitative research uses a purposive sampling method, with primary data collected through questionnaires distributed to auditors at Public Accounting Firms in the Medan area. The study sample consists of 80 auditors, and the data were processed using the SMARTPLS 4.0 application. The results of the study indicate that Audit Tenure and Audit Capacity Stress have a positive influence on Audit Quality, while Audit Fee and Audit Delay show no significant effect on Audit Quality.